2019
DOI: 10.1097/jnr.0000000000000309
|View full text |Cite
|
Sign up to set email alerts
|

Nonadherence in Hemodialysis Patients and Related Factors: A Multicenter Study

Abstract: Background Nonadherence to dietary and fluid restrictions, hemodialysis (HD), and medication treatment has been shown to increase the risks of hospitalization and mortality significantly. Sociodemographic and biochemical parameters as well as psychosocial conditions such as depression and anxiety are known to affect nonadherence in HD patients. However, evidence related to the relative importance and actual impact of these factors varies among studies. Purpose The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
44
3
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(98 citation statements)
references
References 32 publications
6
44
3
10
Order By: Relevance
“…Increased interdialytic weight in HD patients causes increased risk of death due to cerebrovascular events and cardiovascular diseases 4 and leads to an increase in morbidity and mortality together with a deterioration of the patient's quality of life. Interdialytic weight gain (IDWG) reflects incompliance with fluid control as a result of the secondary excessive consumption of liquid and food and is an important surrogate outcome 5 . Various studies have reported incompliance with fluid therapy in 30% to 60% of HD patients 5,6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased interdialytic weight in HD patients causes increased risk of death due to cerebrovascular events and cardiovascular diseases 4 and leads to an increase in morbidity and mortality together with a deterioration of the patient's quality of life. Interdialytic weight gain (IDWG) reflects incompliance with fluid control as a result of the secondary excessive consumption of liquid and food and is an important surrogate outcome 5 . Various studies have reported incompliance with fluid therapy in 30% to 60% of HD patients 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Interdialytic weight gain (IDWG) reflects incompliance with fluid control as a result of the secondary excessive consumption of liquid and food and is an important surrogate outcome 5 . Various studies have reported incompliance with fluid therapy in 30% to 60% of HD patients 5,6 . Other factors affecting the compliance with fluid treatment are psychological and social reasons and lack of knowledge about the foods that can be consumed 6 .…”
Section: Introductionmentioning
confidence: 99%
“…9 Despite these risks, 50% of patients are estimated to be non-adherent to at least one aspect of their treatment recommendations. 11 Because of the complexity of dialysis care and the clinical importance of treatment adherence, as well as the association between psychosocial factors and treatment adherence, 12,13 social workers play an important role in helping to educate patients about their treatment and access resources that might help them to improve adherence. 14 However, in order to provide the best care to patients, non-adherent patients must be reliably identified by dialysis providers.…”
Section: Introductionmentioning
confidence: 99%
“…Poor adherence to HD reduces patients' quality of life and brain function and leads to depression, lung edema and chronic anemia (7), as well as higher mortality rate and financial costs on health care systems (8,9). The role of psychological factors has been suggested as the determinants predicting non-adherence behavior in HD patients; however, this factor has not been established (1).…”
Section: Introductionmentioning
confidence: 99%